Optimizing pulsed Nd: YAG laser welding of high-Mn TWIP steel using response surface methodology technique. (December 2019) - Vahiddastjerdi, H.; Rezaeian, A.; Toroghinejad, M.R.; Dini, G.; Ghassemali, E.
Highlights: Laser welding parameters effect on high manganese steel properties were considered. Response surface methodology was used to develop mathematical models. Free defect weld with best strength obtained by using optimal parameters. The mechanical properties and microstructure of optimized specimen was studied. Laser power has the major effect on responses. Abstract: In the present study, the microstructural and mechanical properties of laser beam-welded thin sheet twinning-induced plasticity (TWIP) steel were investigated. The pulsed neodymium: yttrium-aluminum-garnet (Nd: YAG) laser beam welding process parameters were modeled and optimized based on experimental data and statistical analysis using response surface methodology (RSM) technique. Process parameters range, i.e. the power input (2000–3000 W), welding speed (0.2–1 mm/min), and spot size (0.3–0.7 mm) were selected properly in order to obtain the desired mechanical properties. Main effects of each factor along with interaction effect with other factors were determined quantitatively. The predicted and actual values of the mechanical properties compared using analysis of variance (ANOVA) in order to verify the adequacy of the developed model. Optimal laser beam welding parameters were identified as the power input, welding speed and spot size of 2586 W, 0.53 mm/min, and 0.48 mm, respectively. Using parameters in the optimal conditions, a welding joint with tensile load of 2001 N (% 94 strength of the base metal) was obtained. In addition, the welding zone with an average grain size coarser than the one for the base metal and a random texture was identified.